Fluid homeostatic action of dapagliflozin in patients with chronic kidney disease: the DAPA-BODY Trial - Oka, Kentaro; Masuda, Takahiro; Ohara, Ken; Miura, Marina; Morinari, Masato; Misawa, Kyohei; Miyazawa, Yasuharu; Akimoto, Tetsu; Shimada, Kazuyuki; Nagata, Daisuke (Frontiers in Medicine, 2023)
Sodium glucose cotransporter 2 (SGLT2) inhibitors have both glucose-lowering and diuretic effects. We recently reported that the SGLT2 inhibitor dapagliflozin exerts short-term fluid homeostatic action in patients with chronic kidney disease (CKD). However, the long-term effects of SGLT2 inhibitors on body fluid status in patients with CKD remain unclear. This was a prospective, nonrandomized, open-label study that included a dapagliflozin treatment group (n=73) and a control group (n=24) who were followed for 6 months. Body fluid volume was measured using a bioimpedance analysis device. The extracellular water-to-total body water ratio (ECW/TBW), a predictor of renal outcomes, was used as a parameter for body fluid status (fluid retention, 0.400 ≤ ECW/TBW). Six-month treatment with dapagliflozin significantly decreased ECW/TBW compared with the control group (-0.65%±2.03% vs. 0.97%±2.49%, p=0.0018). Furthermore, dapagliflozin This is a provisional file, not the final typeset article decreased the ECW/TBW in patients with baseline fluid retention, but not in patients without baseline fluid retention (-1.47%±1.93% vs. -0.01%±1.88%, p=0.0017). Vasopressin surrogate marker copeptin levels were similar between the control and dapagliflozin groups at 6 months (32.3±33.4 vs. 30.6±30.1 pmol/L, p=0.8227). However, dapagliflozin significantly increased the change in copeptin levels at 1 week (39.0%±41.6%, p=0.0010), suggesting a compensatory increase in vasopressin secretion to prevent hypovolemia. Renin and aldosterone levels were similar between the control and dapagliflozin groups at 6 months, while epinephrine and norepinephrine (markers of sympathetic nervous system activity) were significantly lower in the dapagliflozin group than in the control group. In conclusion, the SGLT2 inhibitor dapagliflozin ameliorated fluid retention and maintained euvolemic fluid status in patients with CKD, suggesting that SGLT2 inhibitors exert sustained fluid homeostatic actions in patients with various fluid backgrounds.